Characterization of circulating immune cells in acute Kawasaki disease suggests exposure to different antigens. (27th August 2020) - Burns, J C; Hsieh, L E; Kumar, J; Behnamfar, N; Shimizu, C; Sivilay, N; Tremoulet, A H; Franco, A
Summary: Kawasaki disease (KD) is an acute pediatric vasculitis of unknown etiology that can cause coronary artery aneurysms, and is the leading cause of acquired heart disease in children. We studied aspects of the innate and adaptive immune response in 17 acute KD children prior to treatment with intravenous immunoglobulin. Distinct patterns within the innate immune response correlated with specific clinical features. Proinflammatory myeloid dendritic cells (mDC) were abundant in four of 17 (23·5%) subjects who were older and manifested severe inflammation with clinical myocarditis and elevated hepatobiliary enzyme levels. Of the nine subjects with low levels of anti-inflammatory, tolerogenic mDC, six had enlarged cervical lymph nodes at diagnosis. In contrast, the adaptive immune repertoire varied greatly with no discernible patterns or associations with clinical features. Two subjects with aneurysms had numerous circulating CD8 + T cells. Ten subjects showed low CD4 + T cell numbers and seven subjects had CD4 + T cells in the normal range. CD4 + T cells expressed interleukin-7 receptor (IL-7R), suggesting repeated antigenic stimulation. Thymic-derived regulatory T cells (nTreg ) and peripherally induced regulatory T cells (iTreg ) were also enumerated, with the majority having the nTreg phenotype. Natural killer (NK) and NK T cell numbers were similar across all subjects. Taken together, the results of the immune monitoring suggest that KD may have multiple triggers that stimulate different arms of the innate and adaptive compartment in KD patients. Thus, it is possible that diverse antigens may participate in the pathogenesis of KD. Graphical Abstract: